2018
DOI: 10.1002/14651858.cd012753.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Xenon as an adjuvant to therapeutic hypothermia in near-term and term newborns with hypoxic-ischaemic encephalopathy

Abstract: Current evidence from one small randomised controlled pilot trial is inadequate to show whether cooling plus xenon is safe or effective in near-term and term newborns with HIE. Further trials reporting long-term neurodevelopmental outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Doycheva et al [ 30 ] demonstrated that G-CSF + Ab improved body weight, reduced brain tissue damage, and improved long-term neurological function when assessed at 96 h and 5 weeks post HI in the neonatal rat pups, as well as conferring greater neuroprotection by depleting neutrophil accumulation, while G-CSF + metyrapone treatment not only lower caspase-3 expression level but also reduce corticosterone levels in neonates after HI injury [ 89 ]. Surprisingly, there has not been any study evaluating combinational therapy of G-CSF and therapeutic hypothermia (TH), as other modalities have been tried and underwent and/or are undergoing clinical trials in neonatal HIE, such as with epo and TH [ 120 122 ], xenon and TH [ 51 , 123 , 124 ], melatonin and TH [ 46 , 47 ], and allopurinol and TH [ 125 ]. Thus, more study is needed to explore and evaluate the neuroprotective effect of G-CSF in combination with therapeutic hypothermia as well as other emerging agents.…”
Section: Combinational Therapy With Other Agentsmentioning
confidence: 99%
“…Doycheva et al [ 30 ] demonstrated that G-CSF + Ab improved body weight, reduced brain tissue damage, and improved long-term neurological function when assessed at 96 h and 5 weeks post HI in the neonatal rat pups, as well as conferring greater neuroprotection by depleting neutrophil accumulation, while G-CSF + metyrapone treatment not only lower caspase-3 expression level but also reduce corticosterone levels in neonates after HI injury [ 89 ]. Surprisingly, there has not been any study evaluating combinational therapy of G-CSF and therapeutic hypothermia (TH), as other modalities have been tried and underwent and/or are undergoing clinical trials in neonatal HIE, such as with epo and TH [ 120 122 ], xenon and TH [ 51 , 123 , 124 ], melatonin and TH [ 46 , 47 ], and allopurinol and TH [ 125 ]. Thus, more study is needed to explore and evaluate the neuroprotective effect of G-CSF in combination with therapeutic hypothermia as well as other emerging agents.…”
Section: Combinational Therapy With Other Agentsmentioning
confidence: 99%
“…For example, Jacobs et al [ 21 ] conducted a Cochrane systematic review of 11 trials (1505 infants) evaluating the effectiveness of therapeutic hypothermia in encephalopathic asphyxiated newborn infants but were unable to analyse several a priori secondary outcomes because these were not reported in the included trials. Likewise, in a review by Ruegger et al [ 32 ] investigating xenon as an adjuvant to therapeutic hypothermia, they judged the risk of attrition bias in the primary outcome as “unclear” due to incomplete outcome reporting. A lack of standardisation in trials limits the ability of researchers and healthcare providers to improve patient treatment and care as any actual benefits or harms of the therapy are not clear due to the substantial differences in outcomes between trials.…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment with therapeutic hypothermia is an effective approach for neonatal H‐I that is supported by evidence from animal and human studies, the rates of death or disability in these patients are still high (Giesinger et al., 2017; Kali et al., 2015; Shankaran et al., 2017). Combination treatments including therapeutic hypothermia and, for example, melatonin, xenon (targeting the acute injury phase), cannabinoids (targeting the subacute phase), and erythropoietin (targeting the repair phase) have shown considerable potential in their ability to exert neuroprotective effects (Balduini et al., 2019; Ruegger et al., 2018; Solevag et al., 2019; Wu et al., 2016). Further clinical trials reporting neurodevelopmental outcomes are necessary.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%